Head of department leadership styles, leadership behaviour and decision making on job satisfaction of university lecturers in North Eastern States of Nigeria - Abdulrasheed, Olowoselu (2018)
University education is essential for Nigeria to improve its human resources, socio-political and economic development. Apparently, quality of education depends on education leaders, particularly university lecturers. An effective head of department in a university will involve the lecturers in decision-making and help them to achieve their job satisfaction. Despite its importance, this idea is insufficiently discussed in universities in north eastern region of Nigeria. This thesis examines the relationship between head of department leadership styles, behaviour, decision-making styles and their possible use as indicators to predict lecturers’ job satisfaction in a specific context of federal universities in north eastern region of Nigeria. A quantitative research design was used in this thesis. Data were collected from 433 lecturers selected through stratified random sampling technique using a survey instrument. SPSS version 22 and Smart PLS 3 were used to analyze data. Result of the study shows a moderate level of lecturers’ job satisfaction. The results further revealed that the head of department leadership style, behaviour and decision making style are positive and significantly related to lecturers’ job satisfaction. Findings from this study revealed that, head of department leadership style, behaviour and decision making are paramount to lecturers’ job satisfaction. More emphasis should be laid on leadership style in terms of democratic leadership style as well as supportive behaviour and decision making style in the context of intuitive and rational decision making style. It is concluded that lecturers’ job satisfaction can be improved through head of department leadership style, behaviour and decision making style.